Faktorer som påverkar lönsamheten vid köp av skogsfastigheter i Norrbotten - Seger, Daniel (SLU/School for Forest Management, 2015)
During the past 20 years, the price of forest estates in Sweden has raised more than the price of timber. The purpose of this study is to investigate if it, despite this development, is possible to buy a forest estate based on economic grounds. Different forest parameters will also be studied to analyse their effect on the profitability. The study is done in cooperation with the company LRF Konsult. Purchase price of 34 forest estates near the coast of Norrbotten, Sweden, has been compared to yield valuation. For the valuation, guidelines from the Swedish author Lantmäteriet was used. For comparison, a valuation with a discount rate that is 2 points of percentage higher than the guidelines was also done. Using the rate from the guidelines, 13 of the investigated estates was sold for a price under, and 21 for a price over the yield valuation. In average, the purchase price was 2,3 percentage higher than the yield valuation. The parameter with greatest impact between purchase price and yield valuation is the proportion of forest that has reached the minimum age for final felling. High proportion of that type of forest has a negative effect of the profitability. Second highest impact the proportion of forest in young ages has. Forest estates with high proportion of young stands is cheaper to buy compared to the yield valuation than estates with low proportion. Using the higher discount rate, the purchase price in average was 88 percent higher than the yield valuation. This rate seems to be higher than the required rate of return the purchasers has. Using this high rate the studied parameters also effect the connection between purchase price and yield valuation differently. High proportion of forest that has reached the minimum age for final felling now effect the profitability in a positive way. High proportion of young forests is on the other hand negative for the profitability. With this discounting rate all of the forest estates was sold for a price higher than the yield valuation.